Laboratory Testing Performance of Hot Mix Asphalt Containing Waste Materials - Susanto, Hery Awan; Mulyono, Bagyo (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. Road conditions are frequently subjected to damage that outlasts the road's design life. One of these is due to the material's mechanical capability, which is insufficient to withstand traffic loads and weather conditions. The incorporation of plastic and tire waste into Hot Mix Asphalt is one of the efforts to improve the material's mechanical quality (HMA). In addition to reducing the asphalt concentration in the mixture, the percentage of plastic and tire debris reduces the environmental impact. The use of plastic and tire waste in HMA can aid in the creation of green roads. The goal of this research is to see how plastic and tire waste affect HMA performance in Marshall testing. The research was conducted by making test samples with variations of waste materials percentage. Then, the Marshall test was carried out. Analysis of test results includes volumetric properties and Marshall characteristics. The test results showed that the addition of plastic and tire waste was able to improve the performance of the HMA mixture. However, the performance of the HMA mixture will decrease due to the influence of water soaking the HMA mixture. The addition of the optimum waste was obtained by 2.5% at the optimum asphalt content of 5.5%.